Genre Analysis of Chief Examiners’ Reports from Selected Colleges of Education in Ghana - Henry Kwao Ayitey; Obed Nii Broohm; Gladys Mimmie Edjah (E-Journal of Humanities, Arts and Social Sciences, 2022)
Although studies on genre abound in the Ghanaian literature, only a few have paid attention to the form and function of Chief Examiners’ Reports on the academic performance of candidates at examinations. To address this gap, the current study analyzes Chief Examiners’ Reports from selected Colleges of Education, covering several disciplines. The study adopts a qualitative descriptive design to examine movement patterns as well as the linguistic devices employed in such reports. Cast in Bhatia’s model of move analysis theory and Kanoksilapatham’s move criteria, the study shows that moves employed include both mandatory and discretionary ones: six (out of the ten) of the moves are mandatory while four are discretionary. Furthermore, the study found that most Chief Examiners’ Reports lack Introduction sections, and there appears to be no standard structure/format in Chief Examiners’ Reports. Regarding stance-taking devices, the study found that only three pronouns, it, they and this were used. It is recommended that Chief Examiners pay critical attention to the Introduction segments of their reports and that a standard format is provided to all Chief Examiners so as to achieve uniformity